Identification of gram-positive haloversatile bacteria in soak liquor samples and observation of their damage to sheepskin by scanning electron microscopy - ÇAĞLAYAN, PINAR (My University, 2022)
Summary In the leather industry, the salting process is applied to raw hides in order to prevent microbial activity. Salted hides and skins are then soaked to re-absorb the water lost during salting and also to clean the salted hides and skins. Due to the organic load, salt and faeces present in the soak liquor, the soak liquor provides a suitable environment for the growth of bacteria. Bacteria that develop on the hide/skin may cause significant damage to these hides and skins. Therefore, the aims of the present study were to examine the pH values and salt saturation of the soak liquor samples, to detect the total counts of haloversatile bacteria, total counts of proteolytic haloversatile bacteria and total counts of lipolytic haloversatile bacteria in the soak liquor samples. Enzyme (amylase, caseinase, lipase, xylanase, cellulase, protease, DNase, pullulanase, urease, oxidase, or catalase) producing haloversatile bacteria were also isolated from these samples and they were identified with 16S rRNA gene sequence analysis. Their metabolic activities such as utilisation of different amino acid and carbon sources were tested. In addition, the damage caused to the skin structure by enzyme-producing haloversatile bacteria were examined using scanning electron microscope. The pH values and salt saturation of the samples were found as 8.80-9.30 and 3.5%- 5.5%, respectively. The total counts of haloversatile bacteria, proteolytic, and lipolytic haloversatile bacteria were respectively detected as 3.8 x 104-1.6 x 106CFU/mL, 1.2 x 104-5.8 x 105CFU/mL, and 6.3 x 104-4.6 x 105CFU/mL. Six haloversatile bacteria were isolated from the samples belonging to five different species such as Terribacillus halophilus, Brevibacterium luteolum, Bacillus australimaris, Bacillus siamensis, and Bacillus mojavensis. Various enzymes such as protease (83%), lipase (83%), caseinase (67%), amylase (50%), cellulase (17%) were produced by the isolates, on the other hand, none were xylanase, DNase, pullulanase and urease positive. Different sugar sources [lactose (100%), D-(+)-dextrose (100%), myo-inositol (100%), D-(+)- cellobiose (100%), adonitol (100%), D-(-)-salicin (100%), dulcitol (100%), D-mannose (100%), xylitol (83%), L-(+)-arabinose (83%), D-mannitol (67%), D-(-)-fructose (67%), D-(+)-trehalose (67%), D-(-)- ribose (50%), D-(+)-melezitose (33%) and sucrose (17%)] and different amino acid sources [L-serine (100%), L-glutamic acid (67%), DL-phenylalanine (67%), trans-4-hydroxy-L-proline (67%), L-proline (67%), glycine (50%), L-ornithine (50%), L-aspartic acid (33%), L- phenylalanine (33%), L-arginine (17%), L-histidine (17%), L-lysine (17%), L-threonine (17%)] were utilised by the isolates. D-sorbitol, D-(+)-galactose, maltose, D-(+)-xylose and D-(+)-melibiose, L-isoleucine, L-cystine, L-alanine, leucine, L-methionine, L-tyrosine and L-valine were not used.
Keywords: Yaşam Bilimleri; Mikrobiyoloji; Temel Bilimler; Life Sciences; Microbiology; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; MİKROBİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; MICROBIOLOGY; MULTIDISCIPLINARY SCIENCES; Mikrobiyoloji (tıbbi); İmmünoloji ve Mikrobiyoloji (çeşitli); Multidisipliner; Sağlık Bilimleri; Microbiology (medical); Immunology and Microbiology (miscellaneous); Multidisciplinary; Health Sciences